GROWTH OF THE BRINE SHRIMP ARTEMIA FED ON OFFSPRING OF THE COPEPOD Tisbe biminiensis VOLKMANN-ROCCO, 1973 - Lima, Lilian Cristine; Souza-Santos, Lília Pereira (Revista Brasileira de Engenharia de Pesca, 2011)
Artemia nauplius is used as food for rearing shrimp and fish larvae. This study investigated the growth of Artemia fed on the copepod Tisbe biminiensis offspring (nauplii and copepodite 2), compared to those fed on the microalgae Thalassiosira fluviatilis. Artemia nauplii (45 individuals) were stocked in vessels containing 500 mL of seawater and 34 salinity. The vessels were maintained at 28ºC, 13 h light/11 h dark photoperiod and provided with aeration. The culture period was 11 days. The Artemia were fed on microalgae (10,000 cells.mL-1) for four days. On the 5th day two diets were supplied to the Artemia: copepod offspring (10 copepod.mL-1) and microalgae (20,000 cells.mL-1). No significant difference was found in mean survival between diets. The final length of the Artemia fed with copepod diet was significantly higher than Artemia fed with the microalgae diet. The final dry weight of the Artemia did not differ significantly between diets. It can be concluded that T. biminiensis offspring is an alternative food for the culture of Artemia.